Analisa Yuridis Putusan 264/Pid.Sus/2021/PN Mjk tentang Tindak Pidana Perdagangan Orang dalam Perkawinan (Studi Kasus pada Pengadilan Negeri Mojokerto) - Mardiyani, Sindi Mega; Rosnawati, Emy (Indonesian Journal Publisher, 2024)
The victims of the crime of trafficking in persons in marriage are experienced by women. Therefore, victims of the crime of trafficking in persons in marriages must obtain maximum protection. The purpose of this study is to identify and explain and analyze the decision No. 264/Pid.Sus/2021/PN Mjk. This type of research is normative juridical research using the statue approach and case approach, primary and secondary sources of legal material and deductive analysis. The results of this study indicate that the application of criminal law to offenses in Decision 264/Pid.Sus/20201PN Mjk is not in accordance with Law no. 21 of 2007 concerning the eradication of the crime of trafficking in persons and Law no. 1 of 1974 concerning marriage. By imposing a sentence, the judge makes judgments that are in accordance with the facts and disclosures in court. but both in terms of substance and form of testing, it is not in accordance with the current law. In this case, the defendant is sentenced to 1 (one) year in prison. The benefit of this research is that the public knows and obtains an explanation regarding the analysis of the decision Number 264/Pid.Sus/2021/PN Mjk.